PENGARUH KOMUNIKASI PEMASARAN TERINTEGRASI DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN PADAHOTEL GRAND ZURI PEKANBARU - Ruth Anugrah Simangunsong; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted at Hotel Grand Zuri Pekanbaru, the purpose of this study was to determine the effect of integrated marketing communication and corporate image to customer loyalty in Hotel Grand Zuri Pekanbaru. integrated marketing communication and corporate image as an independent variable (